MFI2 upregulation promotes malignant progression through EGF/FAK signaling in oral cavity squamous cell carcinoma - Wei-Chen Yen; Kai-Ping Chang; Cheng-Yi Chen; Yenlin Huang; Ting-Wen Chen; Hsing-Wen Cheng; Jui-Shan Yi; Chun-Chia Cheng; Chih-Ching Wu; Chun-I Wang (Cancer Cell International, 2023)
Abstract Oral squamous cell carcinoma (OSCC) is the predominant histological type of the head and neck squamous cell carcinoma (HNSCC). By comparing the differentially expressed genes (DEGs) in OSCC-TCGA patients with copy number variations (CNVs) that we identify in OSCC-OncoScan dataset, we herein identified 37 dysregulated candidate genes. Among these potential candidate genes, 26 have been previously reported as dysregulated proteins or genes in HNSCC. Among 11 novel candidates, the overall survival analysis revealed that melanotransferrin (MFI2) is the most significant prognostic molecular in OSCC-TCGA patients. Another independent Taiwanese cohort confirmed that higher MFI2 transcript levels were significantly associated with poor prognosis. Mechanistically, we found that knockdown of MFI2 reduced cell viability, migration and invasion via modulating EGF/FAK signaling in OSCC cells. Collectively, our results support a mechanistic understanding of a novel role for MFI2 in promoting cell invasiveness in OSCC.